The influence of motivational orientations on academic achievement among working adults in continuing education - Lee, Pei-Ling; Pang, Vincent Ah Fook (Taylor and Francis Ltd., 2014)
This paper reports on a study of five motivational orientations in continuing education among working adults. The influence of motivational orientations on their academic achievement was identified. The study involved 159 working adults who enrolled into part-time programs in an Open University in Sabah. Boshier's Education Participation Scale (EPS) and Neill's The University Students Motivation and Satisfaction Questionnaire 2 (TUSMSQ2) were adapted to form a thirty-item questionnaire, which was used to collect data about their motivational orientations, that is, personal development, career advancement, social pressure, social and communication improvement, and escapism. Analysis based on an Item-Response model reaffirmed the content validity of items in the questionnaire. The findings indicated that these working adults were highly motivated by career advancement in continuing education compared with the other four motivational orientations. However, the motivational orientations in continuing education varied based on their age, prior education level and length of working experience. Moreover, it was found that adults with higher motivation of personal development tended to perform better in their part-time learning. Some recommendations and directions for future studies are discussed.